A Worthy Contribution to the People of Uzbekistan in the Victory Over Fascism in World War II (Based on the Press of Ferghana Valley) - Dildora Valisherovna, Alinazarova (International Journal of Psychosocial Rehabilitation, 2020)
This article covers a wide range of analyses of archival sources and periodicals of the Ferghana Valley and discusses the issues of the modern approach in highlighting the problems of the history of the Second World War. In addition, the article highlights the topics of "a man in a war," "military everyday life," and the factors of the Great Victory. The article also refers to the message of the president of our country, Shavkat Mirziyoyev, to the Oliy Majlis, namely his speech on preserving the memory of the war.